Thank you for the opportunity to help you with your question!

x + y + z = 4 --------------------(1)

2x - 3y + 2z = -2 ----------------(2)

4x + y - 3z = 3 ------------------(3)

(1) x 2 - (2) ===> 2y - (-3y) = 8 - (-2)

5y = 10

y = 2

(1) x 4 - (3) ====> 4y - y + 4z - (-3z)= 16 - 3

3y +7z = 13

3(2) + 7z = 13

7z = 7

z = 1

Plug y =2, z = 1 into (1)

x + 2 + 1 = 4

x = 1

Therefore, x = 1, y = 2, z = 1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up